Towards a Comprehensive, Empirical Model of Language Assessment Literacy across Stakeholder Groups: Developing the Language Assessment Literacy Survey. Issue 1 (1st January 2020) - Kremmel, Benjamin; Harding, Luke
ABSTRACT: While scholars have proposed different models of language assessment literacy (LAL), these models have mostly comprised prescribed sets of components based on principles of good practice. As such, these models remain theoretical in nature, and represent the perspectives of language assessment researchers rather than stakeholders themselves. The project from which the current study is drawn was designed to address this issue through an empirical investigation of the LAL needs of different stakeholder groups. Central to this aim was the development of a rigorous and comprehensive survey which would illuminate the dimensionality of LAL and generate profiles of needs across these dimensions. This paper reports on the development of an instrument designed for this purpose: the Language Assessment Literacy Survey. We first describe the expert review and pretesting stages of survey development. Then we report on the results of an exploratory factor analysis based on data from a large-scale administration (N = 1086), where respondents from a range of stakeholder groups across the world judged the LAL needs of their peers. Finally, selected results from the large-scale administration are presented to illustrate the survey's utility, specifically comparing the responses of language teachers, language testing/assessment developers and language testing/assessment researchers.